Forms of aggression, peer relationships, and relational victimization among Chinese adolescent girls and boys: roles of prosocial behavior - Wang, Shujun; Zhang, Wei; Li, Dongping; Yu, Chengfu; Zhen, Shuangju; Huang, Shihua (Frontiers in Psychology, 2015)
Through a sample of 686 Chinese adolescents (mean age = 13.73 years; 50% girls), we examined the compensatory and moderating effects of prosocial behavior on the direct and indirect associations between forms of aggression and relational victimization mediated by peer relationships among adolescent girls and boys. The results indicated that only adolescent girls’ relationally aggressive behaviors could be directly linked with their experiences of relational victimization, and both relationally and overtly aggressive adolescent boys and girls might be more often rejected by their peers, which, in turn, could make them targets of relational aggression. Next, we found that prosocial behavior indirectly counteracts the effects of aggression on relational victimization through reducing adolescents’ peer rejection and promoting adolescents’ peer attachment. In addition, relationally aggressive girls with high levels of prosocial behavior might be less rejected by peers; however, they might also have lower levels of peer attachment and be more likely to experience relational victimization. Last, adolescent boys scored higher on risks, but lower on the protective factors of relational victimization than girls, which, to some degree, might explain the gender difference in relational victimization. Finally, we discussed the theoretical and practical implications of these findings.